Measuring Gross Motor Development Quotient Scores Among Rural, Urban, and Indigenous Elementary Schools’ Students - Abdullah, Borhannudin; Mustakim, Siti Salina; Supranie a/p Airak, 3Suphasara; Wen, Ang Xiao; Sheng, Hon Jia; Arpa, Arni Nurfatin (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to identify differences in the scores of students’ gross motor development from different school locations. This study was an ex post facto study involving 69 respondents. The Test of Gross Motor Development (TGMD-2) instrument was utilized to obtain raw data. 12 skills (locomotor: 6, manipulative: 6) were analyzed based on the performance criterion to obtain the raw scores of the study. The raw scores obtained were transcribed to obtain Locomotor Standard Scores (LSS), Manipulative Standard Scores (MSS), and Gross Motor Development Quotient (GMDQ) scores. The scores were analyzed descriptively to obtain the mean and standard deviation of the variables. ANOVA analysis was performed to compare the mean scores on the development of students’ gross motor skills according to different school locations. Descriptive analysis showed that students in rural school (M = 98.4348, SD = 10.268) had the highest mean for GMDQ compared with urban school (M = 76.5217, SD = 11.102) and indigenous school students (M = 85,000, SD = 5.427). Pupils in urban schools get the lowest scores in the developmental stages of motorcycle abuse. There was a significant difference F (18, 50) = 1.790, p = 0.05 for GMDQ scores between urban, rural, and indigenous schools. Post hoc analysis using Games-Howell was performed to see more clearly the differences between groups. The mean difference in mean scores occurred between rural and urban schools with a mean value of 21,913 and a mean difference value of p = .001 was similar to the difference between rural and indigenous schools with a mean of 13.434 and a mean difference value of p = .001. Whereas, the mean difference between urban schools and indigenous schools was low with mean value of 8.478 and significant difference p = .007. Findings indicated that there is a significant increase in motor development for each student according to the location of the school, but their development is not consistent with chronological age. The GMDQ score shows that the gross motor development of all students in different schools is still below average.